ANALISIS TRANSFORMASI ISI PENAFSIRAN MUHAMMAD ABDUH DALAM TAFSIR AL-MANAR PRA DAN PASCA GENERASI MUFASSIR - Fatyucha, Dedek Suci; Kamal, Muhamad Ali Mustofa (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This writing was motivated by the emergence of the book Tafsir Al-Manar in the 20th century, which was a very popular book at that time both in terms of the popularity of the author's character and in terms of the quality of the content of the interpretation. Tafsir Al-Manar is basically the work of three Islamic figures, namely Sayyid Jamaluddin Afghani, then Sheikh Muhammad Abduh and Sayyid Muhamamd Rasyid Ridha. Before the author focuses on the formulation of the problem considering that there are irregularities regarding the author/originator of this book, whether it is purely the work of Muhammad Abduh or Muhammad Rasyid Ridha. The author will briefly touch on several issues related to the interpretation of these two figures. The focus of this writing is stated in the problem formulation: 1) How was the transformation of the content of interpretation carried out by Muhammad Abduh before the mufassir generation? 2) What was the transformation of the content of interpretation carried out by Muhammad Rasyid Ridha after Muhammad Abduh's interpretation? These two problems will be focused on according to their respective principles. This type of research is qualitative in nature, for the time being it is the object of study so that this article can be formed using literature study and then analysis is carried out. This research focuses on literature data sources in the form of documents or written sources. Meanwhile, the aim of this research is to look at the changes in interpretation made by the two figures in accordance with the role of both reason and social conditions used by Muhammad Abduh.